INTEGRASI STRATEGI INOVASI DALAM PENGEMBANGAN KURIKULUM SATUAN PENDIDIKAN DI SEKOLAH DASAR - Munira, Bunga Syafiq; Sukiman, Sukiman (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
Curriculum development is a key element in education, particularly at the elementary school level. A well-designed curriculum must be able to respond to contemporary challenges and prepare students with comprehensive 21st-century competencies. This study employed a qualitative descriptive literature review method to examine innovative strategies in elementary school curriculum development. The main focus is on the implementation of innovative learning models such as Student-Centered Learning (SCL), Problem-Based Learning (PBL), and Project-Based Learning (PjBL), which emphasize creativity, collaboration, and active student engagement. Curriculum development is not only a technical process but also contains anticipatory values toward social change and technological advancement. The success of curriculum innovation depends heavily on collaboration among stakeholders, including teachers, students, principals, and the community. The application of these innovative strategies is expected to improve learning quality, character development, and students’ life skills. In conclusion, this study highlights the importance of continuous and innovative curriculum strategies as a response to global challenges and rapid changes in order to achieve better educational quality.